Impacts of Intermittent Fasting on weight loss - Torres, Marina Tosi (2022)
Intermittent fasting (IJ) is a term that covers popular protocols and can be subdivided into 3 categories, such asalternate day fasting, all-day fasting, and time-restricted feeding. JI has received a considerable increase in interest as a strategy for weight control and/or improving metabolic health. With these strategies, eating patternsand food intake schedules are altered so that individuals undergo repeated periods of fasting. This review providesa commentary on the literature, focusing on the effects of JI to determine if they are effective in improving body composition and clinical markers of health associated with disease. In review, the studies point to JI as a safe strategy for weight loss, positively impacting other health parameters as well. There is still much to learn about intermittent fasting (in its various forms); however, the findings to date serve to highlight promising avenues for future research.